Identification of friction models for precise positioning system in machine tools - Chiew, T. H.; Zamberi, Jamaludin, Dr; Ahmad Yusairi, Bani Hashim, Dr.; Nur Aidawaty, Rafan; Abdullah, L. (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis, Malaysia.